Planning of Vegetative Structures for Coastal Protection Based on Analysis of the Results of Coastal Substrate in Palu Bay - Saraswati, Suprabadevi Ayumayasari; Watiniasih, Ni Luh; Moerwanto, Arie Setiadi; Husnayaen, Husnayaen (Advances in Tropical Biodiversity and Environmental Sciences, 2022)
An earthquake followed by a tsunami occurred on September 28, 2018, in Central Sulawesi. National Disaster Management Agency recorded that 2,113 people died from the earthquake and tsunami, spread over 1,703 people in Palu City, 171 people in Donggala Regency, 223 people in Sigi Regency, 15 people in Parigi Moutong Regency, and Pairskayu Regency with a total of 15 people. 1 person. According to satellite imagery data obtained [2], damage to buildings that occurred in Palu City reached 2,403 buildings and caused the paralysis of Palu City from various aspects, around 70,000 people were accommodated in temporary shelters. Structural mitigation efforts to reduce the impact of damage from natural disasters can be done naturally or artificially. One of the natural structural mitigation efforts in the coastal area of ??Palu City is the creation of a coastal green belt or generally called a Greenbelt. Planting coastal vegetation and mangroves and maintaining existing coastal forest ecosystems is a disaster mitigation effort. Coastal forest ecosystems and mangroves have strong and sturdy root systems that can grip the deepest soil layers. The canopy is flat and dense, and dense at all times, making coastal forests and mangroves an ideal natural protection against the threat of disasters in coastal areas. The purpose of this research is to plan the formation of coastal forests (Planning Vegetative Structure for Coastal Protection) in Palu City Bay. The method used in this research is a descriptive method, namely by field observation, which is carried out to determine the existing condition of vegetation in the coastal area of ??Palu Bay. Based on the results of the analysis, at 23 measurement points, it was found that the thickness of the fine sediment at the bottom of the water ranged from 1-10 cm, while the results of the analysis of the thickness of the coarse sediment ranged from 1-26 cm. The sediment population in Palu City has the characteristics of Gravel (gravel) and Sand (sand). The potential content of TSS in the water column reaches 188 mg/L.